All-cause mortality among Japanese whose cohabiting partners are diagnosed with cancer: the Ohsaki Cohort 2006 study. (3rd April 2019) - Nakaya, Naoki; Sone, Toshimasa; Tomata, Yasutake; Nakaya, Kumi; Hoshi, Masayuki; Shimizu, Ken; Tsuji, Ichiro
Abstract: Background: It has been noted that not only adverse psychosocial health effects but also mortality might increase for a person living with a spouse with cancer. This study examined the association between a partner's cancer diagnosis and mortality among a Japanese population. Methods: In December 2006, a survey was conducted on participants aged 40 years or older who were residing in northeastern Japan. We identified couples using municipality-specific household ID numbers by searching public records and confirmed partner's cancer diagnosis after the baseline measurement using regional cancer registration information. After following up for a maximum of 4.0 years with the participants regarding mortality and emigration by reviewing the Residential Registry Record, we used Cox's proportional hazards regression to estimate the hazard ratio (HR) of all-cause mortality. Results: We identified 25, 938 participants (12, 969 pairs) and included them in the analyses. A total of 1, 308 (5.0%) participants had partners with a cancer diagnosis after baseline. The study found no association between a partner's cancer diagnosis and all-cause mortality; multivariable HRs of all-cause mortality for individuals in exposed subjects compared with those in unexposed subjects were 1.35 (95% confidence interval [CI] = 0.99–1.83; p = .055). Contrarily, sensitivity analyses of mortality attributed to having partners diagnosed with cancer based on the time since entry showed that all-cause mortality significantly increased only within one year from spouse cancer diagnosis; HR = 2.18 (95% CI = 1.44–3.30; p < .01). Conclusions: Our findings reveal that the mortality rate from partner's cancer diagnosis was significantly high during the early period of diagnosis and multidisciplinary teams for cancer treatment might be important for preventing death among the partner.